Structural heterogeneity in capitalism : a view from the Marxist abstract labor theory of value (2017)
This text deals with the analysis of the phenomenon of heterogeneity in capitalist economies with the presence of sectors that are known, in different theoretical traditions, as "informal", "marginality", "popular economy", etc. This is made with Marxist categories and from the "New Approach" paradigm (or the "Abstract Labor Theory of Value". The node of the analysis is focused in the use of two notions: the coexistence of different "forms of production" in economies dominated by the capitalist mode of production, and the assimilation, in analytical terms, of these alternative non-capitalist forms of production to the Marxist category of Simple Commodity Economy. We analyze the role of simple commodity production in the basic operation of the capitalist economy, especially in the operation of the proletarianization and wage setting: we analyze the conditions of the coexistence of capitalist and petty commodity producers in a same market; and made some exploration on the articulation of the phenomenon of unemployment in an economy that includes both mentioned forms of production.